Extraction, Fractionation, And Antioxidant Examination Of Polyfloral Honey Originated From Bone Prefecture South Sulawesi Province - Mandey, Fredryk W; Handayani, Endah; Nanda, Wahyuni Eka; Noor, Alfian (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2019)
The aim of this research to isolate and identify and to test the antioxidant activity of extract and fraction of polyfloral honey originated from Bone regency, South Sulawesi. The results showed that methanol gave results in flavonoid, tannin, saponnin, steroid, and alkaloid with IC50 value of DPPH method of 683,153 µg/mL. DCM extract gave positive results for tannin, steroid and alkaloid with IC50 values of 701,743 µg/mL. n-hexane extract positively contains tannin and alkaloid with IC50 1709,536 µg/Ml, water extract positevely contains tannin, sapponin steroid, alkaloid with IC50 value 1698,345 µg/mL. Pure honey contains all aspects tested with IC50 values 2826,471 µg/mL. This showed extracts and sample have weak antioxidant activity.